1999
DOI: 10.1007/s004490050689
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic digestion of the vegetable fraction of municipal refuses: mesophilic versus thermophilic conditions

Abstract: The phenomena limiting the anaerobic digestion of vegetable refuses are studied through batch tests carried out using anaerobic sludge previously selected under either mesophilic (37 °C) or thermophilic (55 °C) conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…regarding the biogas production at mesophilic and thermophilic conditions. Converti et al (1999) found that passing from mesophilic to thermophilic conditions for the digestion of vegetable fraction of refuses is responsible for a slight deceleration of methane production but remarkably enhances both methanation yield and methane content of biogas. Vindis et al (2009) reported a decrease in solid retention time and increase in biogas production from anaerobic digestion of maize silage under thermophilic conditions.…”
Section: Influence Of Temperaturementioning
confidence: 98%
“…regarding the biogas production at mesophilic and thermophilic conditions. Converti et al (1999) found that passing from mesophilic to thermophilic conditions for the digestion of vegetable fraction of refuses is responsible for a slight deceleration of methane production but remarkably enhances both methanation yield and methane content of biogas. Vindis et al (2009) reported a decrease in solid retention time and increase in biogas production from anaerobic digestion of maize silage under thermophilic conditions.…”
Section: Influence Of Temperaturementioning
confidence: 98%
“…The anaerobic digestion technology, properly implemented in an agro, municipal or industrial technical reality, can also be used to control malodorus emissions. The stabilized biomass can also be utilized as an excellent soil conditioner after appropriate treatment (Converti et al, 1999). The principle of a closed circuit is strengthened because the nitrogen hold strong by the system (MÖller et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Anerobic digestion has many benefits-it produces biogas rich in methane, which can be used to produce electricity and hot water [14][15][16], and emits lesser greenhouse gases (e.g., CH 4 , N 2 O) and NH 3 [17]. In addition, during AD, the waste is converted to a valuable effluent that can be used in agriculture, because of its high nutrient as well as organic matter contents [14,18].…”
Section: Introductionmentioning
confidence: 99%